The Transformation of Valancy: A Psychoanalytic Study of Personality Structure in The Blue Castle - Afia, Ilmi Alfan (English Literature Study Program, 2024)
Personality structure is one of the unique factors possessed by humans. It is the result of the interaction between personality structures, namely id, ego, and superego. One of the novels by L.M. Montgomery entitled The Blue Castle is one of the novels that implements how the depiction of personality structure in a character. The novel is the main data source in this research, which focuses on analyzing the personality structure of the main character in the novel (Valancy). The goal is to find out how the personality structure is described in Valancy's character and and how Valancy's personality structure influences her character development. The researcher uses a literary psychoanalysis approach with textual studies to analyze the data and applies Sigmund Freud's personality structure theory. Personality structure is the interaction between id, ego and superego components that can influence human behavior. Valancy experiences a series of internal and external conflicts in the story. Requires Valancy to be able to get through the various conflicts she experiences. Thus, making her personality structure interact with each other, such as the ego that realizes the id, as well as the role of the superego in showing her moral values. The description of Valancy's personality structure is illustrated in how the desires, realities and moral values that exist in her, which then affect how her character develops. Changing Valancy into a brave, confident and risk-taking figure who is described as a shy, oppressed and less confident woman.